Covid-19, Trust, And Vulnerability In North Halmahera District of Indonesia - Yerik Afrianto Singgalen (Universitas Muhammadiyah Ponorogo, 2021)
Trust is an aspect that is very vulnerable to changes in the element of social capital. The loss of trust impacts the networks and norms accumulated to maintain forms of social capital. During the Covid-19 pandemic, the government limiting individuals' distance through the jargon of